Humanization of Islamic Sciences: Integration of the Covid-19 Pandemic Against Kuntowijoyo's Social Social Concept - Muhammad Ramdhani Arfan; Dewi Maghfirotus Salami (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2021)
The Covid-19 pandemic created very complex problems around the world. The prophetic social concept brought religious values to played an important role in the development of human civilization. The purpose of this study was to integrated the Covid-19 pandemic perspective of Kuntowijoyo's prophetic social approach (Humanization, Liberation, and Transcendence) using literature study methods and the presentation of qualitative data. The attitude of humanization could be demonstrated by upholding human value, both patients, family, and others. Liberation gave the meaning of freedom, in the case Covid-19 pandemic was shown in the release of routine activities that make the immune system decreased and applied it to complying government's advice related to Covid-19. While transcendence was the base of humanization and liberation that would bring human being closer to God. Patience in facing the Covid-19 pandemic would give a rising to a higher degree in the presence of the One Almighty God.